IMPACT OF AQUATIC REHABILITATION AND ELASTIC BANDS FOR A PARTIAL TEAR OF KNEE MEDIAL COLLATERAL LIGAMENT OF MARTIAL ARTS PLAYERS IN KHANAQIN CLUBS - Hani Khaleel Ibraheem (Universitas Negeri Jakarta, 2025)
Background. Players are prone to various sports injuries that prevent them from achieving their highest performance. The likelihood of injury increases with increased training load, as this load is not in line with the athlete's ability and training intensity. Objectives. The research aims to study the effectiveness of a program based on in-water rehabilitation. And use tapes Rubber in processing Injury partial ligament tear of the knee joint For players Arts combat in Clubs Khanaqin. Method. The researcher used the experimental method for two experimental groups with pre- and post-measurement. The first group was subjected to treatment in an aquatic environment and the second was subjected to treatment with elastic bands. The research sample was deliberately selected and amounted to (8) male players and they were divided into two experimental groups, each group had (4) players. After collecting and statistically processing the data, the results showed that both programs had a positive impact on the rehabilitation of those injured with a partial tear in the internal ligament of the knee. Results. The results demonstrated statistically significant improvements, the rehabilitation program also contributed to improving the thigh circumference, increasing muscle strength, expanding the range of motion, and reducing pain levels. This was reflected through the clear statistical differences in the results of the post-measurements of the two groups. Conclusion. The rehabilitation approach using elastic bands and aquatic medium has a positive effect on rehabilitation of a tear. The method prepared using elastic bands has a better effect in developing muscular strength of thigh muscles. Effectiveness of rehabilitation approach in developing (thigh circumference, muscle strength, movement angles, and reducingdegree of pain), through clear difference in results of post-measurements of two experimental groups.